2021
DOI: 10.1080/14756366.2021.1998026
|View full text |Cite
|
Sign up to set email alerts
|

2-Aminobenzoxazole-appended coumarins as potent and selective inhibitors of tumour-associated carbonic anhydrases

Abstract: We have carried out the design, synthesis, and evaluation of a small library of 2-aminobenzoxazole-appended coumarins as novel inhibitors of tumour-related CAs IX and XII. Substituents on C-3 and/or C-4 positions of the coumarin scaffold, and on the benzoxazole moiety, together with the length of the linker connecting both units were modified to obtain useful structure-activity relationships. CA inhibition studies revealed a good selectivity towards tumour-associated CAs IX and XII ( K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Modifications leading to effective inhibitors should thus consider substitution patterns in positions 6, 7 and 8 of the coumarin. This situation was in fact observed also for the inhibition of the human CA isoforms hCA I-XIV already in the first studies in which coumarins were reported as CAIs 1 , 2 .…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Modifications leading to effective inhibitors should thus consider substitution patterns in positions 6, 7 and 8 of the coumarin. This situation was in fact observed also for the inhibition of the human CA isoforms hCA I-XIV already in the first studies in which coumarins were reported as CAIs 1 , 2 .…”
Section: Resultssupporting
confidence: 62%
“…Comarins were discovered relatively recently to act as inhibitors of the zinc enzyme carbonic anhydrase (CA, EC 4.2.1.1) 1 . Unlike all other inhibitor classes investigated at that time, surprisingly, these compounds were shown to not coordinate to the metal ion from the α-CA active sites (the human isoforms hCA I – XIV were initially investigated for their interaction with these compounds 1 , 2 ) but to bind at the entrance of the active site cavity. In addition, the coumarin lactone ring was found hydrolysed to the corresponding 2-hydroxycinnamic acids (either in cis - or trans geometry) making these compounds the first reported class of pro-drug CA inhibitors (CAIs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously reported methodology was used [ 77 ]. For sulfonamides, deprotonated species were considered.…”
Section: Methodsmentioning
confidence: 99%
“…22 , 23 Recent studies have shown the role of CA inhibitors (CAIs) as a therapeutic hit for other diseases like neuropathic pain, 24 cerebral ischemia, 25 and tumor. 26 The unexpected and novel application of CAIs in synaptic transformation and attentional gating of memory is quite appreciating in the treatment of Alzheimer’s disease. 27 …”
Section: Introductionmentioning
confidence: 99%